Developing Interactive Learning Media Of Français des Affaires Using Google Slides With Pear Deck Add-On - Elvi Syahrin; Wahyuni Sa’dah (BIRCU, 2022)
Learning the Français des Affaires courses online or on-site is considerably monotonous, especially for students of French language Department of UniversitasNegeri Medan. This is indicated by the stunted attention and participation of students in attending lectures. This has an impact on the poor learning achievement for the subject, which in turn is one of the causes of the low language skills of students. Developing a more interesting, interactive and creative learning media such as Google Slides with Pear Deck add-on is basically paramount in order to increase students’ learning outcomes in Français des Affaires. By using Research and Development (R&D) research design with the ADDIE procedural model learning design scheme invented by Lee and Owens (2004), the development of interactive learning media in the Français des Affaires course has produced 9 products of Google presentation slides with Pear Deck-add on. The evaluation results of media experts and material experts show that interactive learning media in the Français des Affaires is very good with an average score of 3.85 (96%) for the feasibility of media and an average score of 3.83 (95%) for the feasibility of material. It means that the media of Français des Affaires is suitable for testing on 5th semester (year 2021) students of the French Language Education Study program of odd semester of the 2023/2024 Academic Year.